Comparative analysis of level II oncoplastic surgery and conventional breast-conserving surgery in breast cancer with a ductal carcinoma in situ component - Celik, Omer; Ozgul, Halit; Cakir, Remzi Can; Lale, Azmi; Yildiz, Turan Can; Aydemir, Erhan; Hark, Betul Dagoglu (Springer Japan Kk, 2026)
Background To investigate the pathological outcomes, re-excision rates, local recurrence, patient satisfaction, and cosmetic results associated with level II oncoplastic surgery (OBS) techniques compared to conventional breast-conserving surgery (BCS) in the treatment of breast cancer with a ductal carcinoma in situ (DCIS) component. Methods Between January 2020 and December 2023, 163 patients with invasive carcinoma associated with DCIS were deemed suitable for breast-conserving surgery. The patients were divided into two groups: those who underwent conventional BCS and those who underwent level II OBS. Results Forty patients underwent level II OBS, while 123 patients underwent conventional BCS. The median age was 50 (range 29-65) years for the patients in the level II OBS group and 52 (range 25-68) years for those in the conventional BCS group. Re-excision was performed in three patients (10%) in the level II OBS group compared to 37 patients (30%) in the conventional BCS group, indicating a statistically significant difference (p = 0.035). The median tumor size was 16 (range 3-45) mm in the OBS cohort and 15 (range 4-50) mm in the BCS cohort. Donut mastopexy was the most commonly performed level II oncoplastic procedure (50%). No statistically significant differences were found between the groups in terms of other demographic and histopathological parameters (e.g., tumor laterality, menopausal status, ER, PR, and HER2 positivity, and E-cadher in expression). According to the BREAST-Q survey, the patients in the OBS group reported higher satisfaction with their breasts, better psychosocial well-being, and improved sexual well-being compared to those in the BCS group, with these differences being statistically significant (p < 0.001). Conclusion In breast cancer with a DCIS component, patients who underwent level II OBS had significantly lower re-excision rates, higher patient satisfaction, and better cosmetic outcomes compared to those who underwent conventional BCS.
Keywords: Level-2 oncoplastic surgery; Breast conserving surgery; Breast surgery; DCIS; Breast cancer